The efficacy and medium-term outcomes of ligament advanced reinforcement system compared with auto-grafts in anterior cruciate ligament reconstruction: At least 2 years follow-up - Ma, Bingxian; Wang, Yongxiang; Xu, Yongsheng (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Graft choice is an important step in the pre-operative plan of anterior cruciate ligament reconstruction (ACLR). The four-strand hamstring tendon (4SHT) is the most widely used auto-graft, while the Ligament Advanced Reinforcement System (LARS) is the newest typical biomaterial for ACLR. The physical activity level (PAL) before injury can affect the efficacy and outcomes of ACLR. This study aims to compare the efficacy and functional outcomes between ACLR using LARS and 4SHT in patients different PALs. Methods: This was a prospective paired case-control study. ACL rupture patients included from January 1, 2017, to December 31, 2019, were subsequently divided into the high and plain PAL groups, according to their baseline PAL before injury. Clinical assessments included: Lachman test, pivot shift test, ligament laxity, Lysholm and International Knee Documentation Committee (IKDC) scores, and rate of returning to sports. The minimum follow-up was 2 years (y). Results: 58 patients had accomplished the 2y follow-up (missing rate: 6.5%). In the high PAL group (n=22), the positive rate of A-P laxity of the LARS subgroup was lower than the 4SHG subgroup (P=0.138), while the Lysholm score (P=0.002), IKDC score (P=0.043), and rate of returning to sports (P =0.010) of the LARS were higher than the 4SHG at 1 y follow-up; the positive rates of A-P laxity (P=0.009), pivot test (P=0.027) were lower in the LARS than the 4SHG at 2 y follow-up. In the plain PAL group (n=36), the positive rate of A-P laxity in the LARS subgroup was lower than the 4SHG at 1 y follow-up (P=0.017); the positive rates of A-P laxity (P=0.001), Lachman (P=0.034) and pivot tests (P=0.034) in the LARS were also lower than the 4SHG at 2 y follow-up, but the IKDC score (P =0.038) and rate of returning to sports (P =0.019) in the 4SHG were higher than the LARS. Conclusions: In patients with high PAL, LARS can acquire better knee stability, sooner functional recovery and returning to sports than 4SHG, while in patients without high PAL, 4SHG acquires better functional outcomes and a higher rate of returning to sports. Level of Evidence : Level 2.